(3GdeSDhdjI GdeOfjI dTQcGJ EfJGL h JhRjY GdJHZ (B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3eMeO Ydj CMeO GdYeGhjs; (3SYjO SdjeGf LHQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3ddhdGjGJ GdeJMOI GdCeQjcjI HGY Whjd aj eLGd ebGVGI UfGYI GdJHZ jeJO deG jbGQH (B60 (3YGekG(B:(3hbO CXgQJ GdJLQHI GdCeQjcjI fLGYI GdJbGVj cCMO COhGJ GSJQGJjLjI ecGaMI GdJHZ HGdMO ef fTGWGJ gPg GdUfGYI hJhajQ GdJYhjV GdedGFe ddeJVQQjf ef GSJgdGc efJLGJgG(B:(3djKhQ GdJSGDd ef HYO ajeG GPG cGf dbGfhf eSDhdjI GdefJL Cf jhaQ GdCSGS GdbGfhfj deKd gPG GdJYhjV(B:(3hGKHGJ bOQI gPG GdbGfhf Ydi JYhjV GdfbU aj GdJTQjYGJ GdfGXeI dfTGW Jdc GdUfGYI(B:(3hGdYed Ydi JYRjR fXGe GdeSDhdjI GdeOfjI HTcd YGe dCOGA GdOhQ GdefhW HgG aj gPG GdeLGd(B:(3heMGhdI GdCNP HGdJLGQH GdYGdejI aj ebGVGI UfGYI GdJHZ aj YGdefG GdYQHj cCMO SHd Jehjd GdfabGJ hGdJcGdja GdeJQJHI Ydi YdGL GdCeQGV GdeQJHWI HGdJONjfs
The United States of America already have a 60-year history of litigation against the tobacco industry. In the last decade in particular, tobacco litigation has been a tool in tobacco control strategies aimed at limiting the activities of tobacco companies and providing redress to persons who have been injured as a result of their use of tobacco products, the question therefore arises whether product liability law could offer a better avenue to obtain compensation for their losses. and illustrates how product liability law can ensure that tobacco manufacturers are made accountable even in the absence of specific legislative provisions, then studying the best ways to strengthen product liability of tobacco manufacturers and importers in the Arab world, as well as their liability for financing the health costs arising from tobacco consumption
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfi (B2015.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B564-608s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3bhGfjf hJTQjYGJs; (3eUQs -- (3bhGfjf hJTQjYGJs; (3GdSYhOjI s -- (3bhGfjf hJTQjYGJs; (3GdJHZs; (3GdeSDhdjI GdeOfjIs; (3TQcGJ GdEfJGL h GdJhRjYs; (3UfGYI GdJHZs; (3CVQGQ GdJHZs; (3bGfhf GdYbO s; (3XghQ GdEgeGds; (3eSDhdjI GdefJLs; (3ebGVGI GdJHZ s; (3JYjH GdSLGFQ s; (3MXQ GdJONjfs; (3GdJLQHI GdSYhOjIs; (3CeQjcGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs